New technologies and development - Johnston, Ann ed. (UNESCO ParisFR, 1986)
Presents the papers emanating from a collloquium held at UNESCO Headquarters in 1984. Looks at themes such as information technologies and telecommunications; biotechnologies in farming and food systems; health care technologies and helath care delivery systems; new energy technologies and systems; and, technological advance and educational change.